2014
DOI: 10.1016/j.psychres.2014.05.045
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to investigate the induction and manipulation of learned helplessness in healthy adults

Abstract: Eliminating the controllability of a noxious stimulus may induce a learned helplessness (LH) that resembles aspects of depression and post-traumatic stress disorder (PTSD). This study examined whether repetitive transcranial magnetic stimulation (rTMS) of the left dorsolateral prefrontal cortex (DLPFC) promotes resilience in an aversive stimulus model of LH. All 55 participants were told that an undisclosed sequence of button presses would terminate an aversive stimulus on their forearm. In truth, only half ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Thus, cognitive abilities play a role in the IGT at the later trials of the task. Classical studies indicate that exposure to uncontrollability leads to disturbances in cognitive tasks (Hiroto and Seligman, 1975 ; Miller and Seligman, 1975 ) and a recent study also demonstrated a tendency in that direction (Taylor et al, 2014 ). Recent research suggests that stress can also lead to reduced performance in cognitive tasks (Starcke et al, 2016 ).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, cognitive abilities play a role in the IGT at the later trials of the task. Classical studies indicate that exposure to uncontrollability leads to disturbances in cognitive tasks (Hiroto and Seligman, 1975 ; Miller and Seligman, 1975 ) and a recent study also demonstrated a tendency in that direction (Taylor et al, 2014 ). Recent research suggests that stress can also lead to reduced performance in cognitive tasks (Starcke et al, 2016 ).…”
Section: Discussionmentioning
confidence: 98%
“…One such possibility is that the observed results could have stemmed from a mechanism akin to “learned helplessness”, resulting from the lack of control induced by corrupted feedback 8 . However, while lack of control is known to impair performance 20,21 , this mechanism cannot explain the increase in cue congruence (CCI). The shift in responses towards cues was not deliberate, since such a shift in response strategy would have given high CCIs (approaching the maximum value of 100, see Materials and Methods).…”
Section: Discussionmentioning
confidence: 99%
“…A prefrontal rTMS study in healthy young adults showed they had increased resilience after even a single session. 45 …”
Section: Discussionmentioning
confidence: 99%